The School-Based Family: Teachers as Parental Figures for Orphans and Vulnerable Children in Ugandan Schools. Issue 2 (17th February 2019) - Taniguchi, Stacy; Warren, Angela; Hite, Steve; Widmer, Mark; Zabriskie, Ramon B.; Nsubuga, Yusef; Mugimu, Christopher
ABSTRACT: The purpose of this study was to examine the possible formation of surrogate families within Ugandan schools, especially among orphans who lack positive development opportunities typically provided by parents. This qualitative study sample of 66 Ugandan secondary school students were selected from eight schools in the Mukono district of Uganda. Findings suggest a potentially widespread family formation pattern between students and their teachers. More than 75% of students interviewed self-identified their teacher as family. Some teachers were able to offer orphans and vulnerable children positive developmental assets and were, therefore, identified as family.